Difference Cultural Structure and Behavior Students in Learning Process - Pamela, Claudia; Villalobosl, Luciana; Peralta, Nadine (SCAD Independent, 2017)
This paper summarizes some observations and reflections on how cultural differences bedeviled my interactions with my students in Universidad de Lima, Peru. Culture is not an abstract force that floats around in space and settles upon us—though given the seemingly subliminal ways it influences us, it can feel like a disembodied, ubiquitous entity. In fact, culture is mediated through a social structure. In general, culture refers to the ways in which different groups of people organize their daily lives within national or ethnic groups, urban neighborhoods, companies and professions, and other settings. Culture includes what people actually do and what they believe. Culture influences greatly how we see the world, how we try to understand it and how we communicate with each other. Therefore, culture determines, to a great extent, learning and teaching styles. When we compare cultures we should not look for differences that make us better or worse than each other. No culture is better than another and no communication style is intrinsically wrong. My teaching and communication styles are deeply rooted in the way I have been socialized and a year of teaching at college reminded me that my students' communication and learning styles were different from mine. Perhaps the most important lesson I learned is that I must adapt to this new environment and change the way I communicate if I wish to be an effective teacher.